Syntheses, structures and properties of metal complexes of bis(2-pyridylmethyl) derivatives of o-, m-, and p-phenylenediamine and aniline - Turba, Sabrina; Justus Liebig University Giessen (My University, 2008)
Syntheses and characterisations of metal complexes with the ligand 1,3-bis[bis(2-pyridylmethyl)amino]benzene(1,3-tbpd) and it s derivatives N, N-bis(2-pyridylmethyl)aniline (phbpa), 2,6-bis[bis(2-pyridylmethyl)amino]-p-cresole (2,6-tpcd) und 1,3,5-tris[bis(2-pyridylmethyl)amino]benzene (1,3,5-hpbt) as well as it s ortho- and para-substituted analogues 1,2-bis[bis(2-pyridylmethyl)amino]benzene (1,2-tbpd) and 1,4-bis[bis(2-pyridylmethyl)amino]benzene (1,4-tbpd) are reported herein. These investigations are based on the previous studies on the complex [Cu2(1,3-tpbd)(H2O)2(ClO4)3]ClO4, which showed quite interesting magnetic behaviour. As briefly described in chapter 2 and 3, the magnetic properties of the copper(II) complexes with the ligand 1,3-tpbd were strongly dependent on the presence of additional ligands/anions. These investigations have been successfully continued in this work and in cooperation with the researchers mentioned in the previous chapters, copper(II), iron(II), nickel(II) and zinc(II) complexes with the ligand 1,3-tpbd could be synthesized and characterized using X-ray diffraction methods. Furthermore, copper(II) complexes with the ligands phbpa, 1,2-tpbd and 1,4-tpbd could be synthesized and furthermore, structurally characterized. The complexes [Cu4(1,3-tpbd)2(AsO4)(ClO4)3(H2O)](ClO4)2 x 2 H2O x 0.5 CH3OH and [Cu4(1,3-tpbd)2(PO4)(ClO4)3(H2O)](ClO4)2 x 2 H2O x 0.5 CH3OH are tetranuclear compounds and in each the arsenate/phosphate ion acts as a bridge between four copper(II) ions. Hence, the Cu(1)...Cu(2)-distances in these compounds are with 4.358/4.226 Å significantly shorter than in the complexes that were synthesized previously. The investigation of the magnetic properties of the complex [Cu4(1,3-tpbd)2(PO4)(ClO4)3(H2O)](ClO4)2 x 2 H2O x 0.5 CH3OH showed the expected paramagnetic behaviour. Furthermore, detailed magnetic investigations on the complexes [CuCl2(phbpa)], [Cu2Cl4(1,3-tpbd)] x 0.84 CH3OH, [{Cu2Cl2(ClO4)(1,3-tpbd)}Cl{Cu2Cl2(OH2)(1,3-tpbd)}](ClO4)2 and [Cu2(OH2)2(S2O6)(1,3-tpbd)]S2O6 x 2 H2O x CH3OH were performed. For the complex [{Cu2Cl2(ClO4)(1,3-tpbd)}Cl{Cu2Cl2(OH2)(1,3-tpbd)}](ClO4)2 theoretical calculations of the DFT type were performed to visualize and evaluate the efficiency of the intramolecular exchange pathways involved. The ligand 1,3-tpbd in its unprotonated as well as in its protonated form could be characterized crystallographically. It is remarkable that the protons (in the protonated compounds [H2(1,3-tpbd)](ClO4)2 and [H2(1,3-tpbd)](CF3SO3)2) are, similar to small metal cations, coordinated between the pyridine nitrogen atoms of the ligand. While the nickel complex shows normal coordination behavior, redox active metal centers such as iron or copper ions demonstrate that 1,3-tpbd is a non-innocent ligand. Interestingly 1,3-tpbd does not coordinate iron(III) ions, instead protonation of the ligand is preferred. Oxidations of iron(II) complexes or copper(I) complexes of 1,3-tpbd led to reaction product mixtures that could not be characterized so far. Theoretical calculations support the formation of a dinuclear side-on copper peroxo complex during the reaction of the copper(I) complex with dioxygen. Intramolecular ligand hydroxylation was not observed during the oxidation reaction, however, preliminary experiments showed the formation of a violet coloured peroxo-intermediate. Unfortunately this reaction could not be reproduced for reasons that are not clear at all. The reaction product that would have formed if an intramolecular hydroxylation reaction would occur during oxidation, a phenolate bridged derivative of the 1,3-tpbd complex, using the ligand 2,6-tpcd, could be synthesized in an independent way. The thus obtained [Cu2(2,6-tpcd)(H2O)(Cl)](ClO4)2 x 2 H2O could be structurally characterized. To increase the complexity of the 1,3-tpbd ligand a further ligand arm was introduced, forming the new ligand 1,3,5-Hpbt. Efforts to obtain the trinuclear copper complex of this ligand were unsuccesfull. However, the precursor compound prepared for the synthesis of this ligand, the protonated 1,3,5-triaminobenzene (that could be structurally characterized), proved to be very interesting for detailed NMR studies.

In dieser Arbeit wird die Synthese und Charakterisierung von Metall-Komplexen mit dem Liganden 1,3-Bis[bis(2-pyridylmethyl)amino]benzol (1,3-tbpd) und seinen Derivaten N, N-Bis(2-pyridylmethyl)anilin (phbpa), 2,6-Bis[bis(2-pyridylmethyl)amino]-p-kresol (2,6-tpcd) und 1,3,5-Tris[bis(2-pyridylmethyl)amino]benzol (1,3,5-hpbt) sowie seinen ortho- und para-substituierten Analoga 1,2-Bis[bis(2-pyridylmethyl)amino]benzol (1,2-tbpd) und 1,4-Bis[bis(2-pyridylmethyl)amino]benzol (1,4-tbpd) beschrieben. Ausgangspunkt war der Komplex [Cu2(1,3-tpbd)(H2O)2(ClO4)3]ClO4, dessen ungewöhnliche magnetische Eigenschaften von großem Interesse waren. Wie in Kapitel 2 und 3 beschrieben, konnten die magnetischen Eigenschaften der bisher dargestellten Kupfer(II)-Komplexe mit dem Liganden 1,3-tpbd durch zusätzliche Liganden/Anionen variiert werden. Im Rahmen dieser Arbeit wurden diese Untersuchungen erfolgreich fortgesetzt und in Kooperation mit den in den jeweiligen Kapiteln aufgeführten Wissenschaftlern konnten Kupfer(II)-, Eisen(II), Nickel(II) und Zink(II)-Komplexe dargestellt und kristallographisch charakterisiert werden. Zudem wurden Kupfer(II) Komplexe mit den Liganden phbpa, 1,2-tpbd und 1,4-tpbd dargestellt und erfolgreich kristallographisch charakterisiert. Bei den Komplexen [Cu4(1,3-tpbd)2(AsO4)(ClO4)3(H2O)](ClO4)2 x 2 H2O x 0.5 CH3OH und [Cu4(1,3-tpbd)2(PO4)(ClO4)3(H2O)](ClO4)2 x 2 H2O x 0.5 CH3OH gelang es erstmals Komplextetramere darzustellen, bei welchen das Arsenat- bzw. das Phosphat-Ion sowohl intra- als auch intermolekular verbrückend zwischen den Kupfer(II)-Atomen wirkt. Zudem wurden detaillierte magnetische Untersuchungen an den Komplexen [CuCl2(phbpa)], [Cu2Cl4(1,3-tpbd)] x 0.84 CH3OH, [{Cu2Cl2(ClO4)(1,3-tpbd)}Cl{Cu2Cl2(OH2)(1,3-tpbd)}](ClO4)2 und [Cu2(OH2)2(S2O6)(1,3-tpbd)]S2O6 x 2 H2O x CH3OH durchgeführt. Für den Komplex [{Cu2Cl2(ClO4)(1,3-tpbd)}Cl{Cu2Cl2(OH2)(1,3-tpbd)}](ClO4)2 wurde ausserdem eine DFT-Rechung durchgeführt, um den Mechanismus des stattfindenden intramolekularen magnetischen Austauschs visualisieren zu können. Erstmals gelang es im Rahmen dieser Arbeit, die Struktur des Liganden 1,3-tpbd, sowohl in reiner als auch in deprotonierter Form kristallographisch zu charakteriseren. Erwähnenswert ist in diesem Zusammenhang, dass die Protonen in den Strukturen X und Y wie kleine Metallkationen zwischen den Pyridin-Stickstoffatomen des Liganden koordiniert sind. Während der beschriebene Nickel (II) Komplex mit dem Liganden 1,3-tpbd normales Koordinationsverhalten zeigt, demonstrieren redox-aktive Metallzentren wie Eisen- oder Kupfer-Ionen, dass 1,3-tpbd durchaus in der Lage ist, an den jeweiligen Redox-Reaktionen teilzunehmen. Interessanterweise, koordiniert 1,3-tpbd beispielsweise keine Eisen(III) Kationen, stattdessen wird eine Protonierung des Liganden bevorzugt. Oxidationen von Eisen(II)- oder Kupfer(I)-Komplexen mit 1,3-tpbd resultieren in Reaktionsgemischen, die bisher noch nicht weiter charakterisiert werden konnten. Theoretische Rechnungen sagen die Bildung eines zweikernigen side-on Kupfer-Peroxo Komplexes bei der Reaktion des Kupfer(I)-Komplexes mit molekularem Sauerstoff voraus und erste Experimente zeigten die Bildung eines violetten Intermediates, was auf die Bildung eines solchen Peroxo-Komplexes hindeutet. Jedoch ließ sich diese Reaktion bislang nicht reproduzieren. Eine intramolekulare Hydroxylierung des Liganden wird hier nicht beobachtet. Das mögliche Oxidationsprodukt einer intramolekularen Hydroxylierungsreaktion, das phenolatverbrückte Derivat des Kupfer(II)-1,3-tpbd Komplexes, konnte auf eigenständige Weise unter Verwendung des Liganden 2,6-tpcd synthetisiert werden. Der so erhaltene Komplex [Cu2(2,6-tpcd)(H2O)(Cl)](ClO4)2 x 2 H2O wurde kristallographisch charakterisiert. Um die Komplexizität des 1,3-tpbd Ligandensystems zu erhöhen, wurde ein weiterer koordinierender Arm eingeführt. Daraus resultierte der neue Ligand 1,3,5-Hpbt. Bisher konnten leider noch keine dreikernigen Kupfer(II) Komplexe mit diesem Liganden dargestellt werden. Die Vorstufe für die Synthese dieses Liganden, 1,3,5-Triaminobenzol Trihydrochlorid, (welches zudem kristallographisch charakterisiert werden konnte) erwies sich als sehr interessantes Untersuchungsobjekt für ausführliche NMR-spektroskopische Analysen.
Synthese, Strukturen und Eigenschaften von Metallkomplexen der Bis(2-pyridylmethyl)-Derivate von o-, m- und p-Phenylendiamin sowie Anilin
Keywords: ddc:540